Contraction Dynamics of Rod Microtissues of Gingiva-Derived and Periodontal Ligament-Derived Cells - Oberoi, Gunpreet; Janjić, Klara; Müller, Anna Sonja; Schädl, Barbara; Andrukhov, Oleh; Moritz, Andreas; Agis, Hermann (Frontiers in Physiology, 2018)
Tissue engineering strategies using microtissues as “building blocks” have high potential in regenerative medicine. Cognition of contraction dynamics involved in the in vitro self-assembly of these microtissues can be conceived as the bedrock of an effective periodontal tissue regenerative therapy. Our study was directed at evaluating the shrinkage in the rod-shaped structure of a directed self-assembly of human gingiva-derived and periodontal ligament-derived cells (GC and PDLC) and developing insights into the potential mechanisms responsible for the shrinkage. GC and PDLC were seeded in non-adherent agarose molds to form rod microtissues. Cells used for the experiments were characterized using fluorescence-activated cell sorting (FACS). To assess the viability, resazurin-based cytotoxicity assays, Trypan blue dye exclusion assay, MTT and Live/Dead staining, and histological evaluation of rods was performed based on hematoxylin and eosin staining. Rod contraction was evaluated and measured at 0, 2, 6, and 24 hours and compared with those from L-929 cells. The role of transforming growth factor (TGF)-beta signaling, phosphoinositide 3-kinase (PI3K)/AKT, and mitogen activated protein kinase signaling was analyzed. Our results show that the rod microtissues were vital after 24 hours. A reduction in the length of rods was seen in the 24 hours period. While the recombinant TGF-beta slightly reduced contraction, inhibition of TGF-beta signaling did not interfere with the contraction of the rods. Interestingly inhibition of phosphoinositide 3-kinase by LY294002 significantly delayed contraction in GC and PDLC rods. Overall, GC and PDLC have the ability to form rod microtissues which contract over time. Thus, approaches for application of these structures as “building blocks” for periodontal tissue regeneration should consider that rods have the capacity to contract substantially. Further investigation will be needed to unravel the mechanisms behind the dynamics of contraction.